Effects of Coculture Fibroblasts and Vascular Endothelial Cells on Proliferation and Osteogenesis of Adipose Stem Cells. (13th January 2022) - Liao, Xinyu; Zhong, Ruiying; Zhang, Hong; Wang, Fuke
Abstract : Background . The development of tissue engineering provides a new method for the clinical treatment of bone defects, but the problems of slow formation and slow vascularization of tissue engineered bone have always existed. Studies have shown that the combined culture system of vascular endothelial cells and adipose stem cells is superior to single cell in repairing bone defects. With the excellent proliferation ability, secretion of synthetic collagen and a variety of regulatory factors and fibroblasts can differentiate into osteoblasts and have the potential to be excellent seed cells involved in tissue engineering bone construction. Objective . To investigate the effects of combined culture of fibroblasts, vascular endothelial cells, and adipose stem cells on proliferation and osteogenic differentiation of adipose stem cells. Methods . The cells were divided into 4 groups: adipose stem cell group, adipose stem cell+vascular endothelial cell coculture group, adipose stem cell+fibroblast coculture group, and adipose stem cell+vascular endothelial cell+fibroblast coculture group. The morphological changes of the cells were observed under an inverted microscope. After 1, 3, 5, 7, and 9 days of coculture, the proliferation of adipose stem cells in each group was detected by a CCK-8 method and the growth curve was plotted. Adipose stem cells in each group were stained with alizarin red and alkaline phosphatase at days 7, 14, 21, and 28. At the third week of coculture, Western blot was used to detect the expression level of bone morphogenetic protein 2 of adipose stem cells in each group. Results and Conclusions . (1) After 14 days of culture, some cells in the adipose stem cell+vascular endothelial cell+fibroblast coculture group fused into clumps and distributed in nests, while the adipose stem cells in the adipose stem cell group had a single cell morphology and no cell clusters were observed. (2) The cell growth curves were basically the same in each group, and the absorbance value increased gradually. The absorbance value of the adipocyte+vascular endothelial cell+fibroblast coculture group was the highest, followed by the adipocyte+fibroblast coculture group and then the adipocyte+fibroblast coculture group. (3) Alizarin red staining showed negative reaction in each group on the 7th day, and a small number of red positive cells gradually appeared in each group as time went on. On the 28th day, red positive cells were found in all groups, and most of them were in the coculture group of adipose stem cells+vascular endothelial cells+fibroblasts, showing red focal. The coculture group of adipose stem cells+vascular endothelial cells and adipose stem cells+fibroblasts was less, and the adipose stem cell group was the least. On day 28 of alkaline phosphatase staining, cells in each group had red positive particles, and the adipose stem cell+vascular endothelial cell+fibroblast coculture group and adipose stem cell+fibroblast coculture group had the most, followed by the adipose stem cell+vascular endothelial cell coculture group and then the adipose stem cell group. (4) Bone morphogenetic protein 2 was expressed in all groups, especially in adipose stem cell+fibroblast coculture group and adipose stem cell+vascular endothelial cell+ fibroblast coculture group. (5) Fibroblast could promote adipose stem cell osteogenic differentiation better than vascular endothelial cells, but the proliferation effect was not as good as vascular endothelial cells. The coculture system of fibroblast combined with vascular endothelial cells and adipose stem cells promoted the proliferation of adipose stem cells and the rapid and efficient differentiation of adipose stem cells into osteoblasts.